Kostume-drevne performances: Kostumers generative og performative potentialer - Østergaard, Charlotte (Peripeti, 2022)
Costume driven performances. Costumes generative and performative potentials This article examines costume driven performances as a growing trend in international performing arts as well as in costume research. It also provides the more detailed analysis of a costume-driven dance performance from the author’s own practice and concludes with considerations about the potential in Danish performing arts.